Implementing Islamic social finance: challenges and proposed solutions - Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah (Edbiz Corporation Limited, 2018)
Social finance is an approach to managing investments that generate financial returns while including measurable positive social and environmental impact. practice, social finance typically involves investments in some forms of socially sensible equity or debt financing, microfinance, and social impact bonds.